Treatment of Mild Cervical Myelopathy: Factors Associated With Decision for Surgical Intervention. Issue 22 (15th November 2019) - Bond, Michael; McIntosh, Greg; Fisher, Charles; Jacobs, Bradley; Johnson, Michael; Bailey, Christopher S.; Christie, Sean; Charest-Morin, Raphaele; Paquet, Jérome; Nataraj, Andrew; Cadotte, David; Wilson, Jeff; et al.
Abstract : Study Design: Prospective Cohort Objective: The aim of this study was to evaluate which demographic, clinical, or radiographic factors are associated with selection for surgical intervention in patients with mild cervical spondylotic myelopathy (CSM). Summary of Background Data: Surgery has not been shown superior to best conservative management in mild CSM comparative studies; trials of conservative management represent an acceptable alternative to surgical decompression. It is unknown what patients benefit from surgery. Methods: This is a prospective study of patients with mild CSM, defined as modified Japanese Orthopaedic Association Score (mJOA) ≥15. Patients were recruited from seven sites contributing to the Canadian Spine Outcomes Research Network. Demographic, clinical, radiographic and health related quality of life data were collected on all patients at baseline. Multivariate logistic regression modeling was used to identify factors associated with surgical intervention. Results: There were 122 patients enrolled, 105 (86.0%) were treated surgically, and 17 (14.0%) were treated nonoperatively. Overall mean age was 54.8 years (SD 12.6) with 80 (65.5%) males. Bivariate analysis revealed no statistically significant differences between surgical and nonoperative groups with respect to age, sex, BMI, smoking status, number of comorbidities and duration of symptoms; mJOA scores were significantly higher in the nonoperative group (16.8 [SD 0.99] vs. 15.9 [SD 0.89], P < 0.001). There was a statistically significant difference in Neck Disability Index, SF12 Physical Component, SF12 Mental Component Score, EQ5D, and PHQ-9 scores between groups; those treated surgically had worse baseline questionnaire scores ( P < 0.05). There was no difference in radiographic parameters between groups. Multivariable analysis revealed that lower quality of life scores on EQ5D were associated with selection for surgical management ( P < 0.018). Conclusion: Patients treated surgically for mild cervical myelopathy did not differ from those treated nonoperatively with respect to baseline demographic or radiographic parameters. Patients with worse EQ5D scores had higher odds of surgical intervention. Level of Evidence: 3 Abstract : The purpose of this study was to evaluate which baseline factors were associated with selection to surgical care in mild cervical myelopathy. Patients treated nonoperatively did not differ with respect to demographic or any radiographic parameters. Patients were more likely to have operative treatment if they had a worse clinical picture. Those treated nonoperatively had significantly higher baseline quality of life and milder symptoms.